2020
DOI: 10.3390/ijerph17051608
|View full text |Cite
|
Sign up to set email alerts
|

Canonical Correlation between Behavioral-Psychological Variables and Predictors of Coronary Artery Disease Prognosis

Abstract: Metabolic syndrome (MetS) and severity of coronary artery disease (CAD) are considered predictors of CAD prognosis. Unhealthy lifestyles and type-D personality are associated with MetS and are potential causes of primary and secondary CAD. In this cross-sectional descriptive study, we aimed to investigate the relationship between behavioral-psychological variables and predictors of CAD prognosis. The behavioral-psychological variable set contained six lifestyle categories and two type-D personality categories.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Finally, several authors have reported significant associations between type D personality (negative affectivity and social inhibition) [464,465] and depressive or irritable temperament [466,467]. The causes of these associations are not fully understood, but in the case of type D personality, adverse lifestyle choices predictive of CVD development appear to be an important factor while irritable temperament is predictive of increased vascular stiffness and hypertension [465,468,469].…”
Section: Socioeconomic Behavioural and Psychosocial Factors In The Dementioning
confidence: 99%
See 1 more Smart Citation
“…Finally, several authors have reported significant associations between type D personality (negative affectivity and social inhibition) [464,465] and depressive or irritable temperament [466,467]. The causes of these associations are not fully understood, but in the case of type D personality, adverse lifestyle choices predictive of CVD development appear to be an important factor while irritable temperament is predictive of increased vascular stiffness and hypertension [465,468,469].…”
Section: Socioeconomic Behavioural and Psychosocial Factors In The Dementioning
confidence: 99%
“…Finally, several authors have reported significant associations between type D personality (negative affectivity and social inhibition) [ 464 , 465 ] and depressive or irritable temperament [ 466 , 467 ]. The causes of these associations are not fully understood, but in the case of type D personality, adverse lifestyle choices predictive of CVD development appear to be an important factor while irritable temperament is predictive of increased vascular stiffness and hypertension [ 465 , 468 , 469 ]. There is also an argument that a type D personality and/or an irritable temperament make an individual more susceptible to the effects of environmental stressors and experience the physiological effects of chronic stress such as increased glucocorticoid receptor resistance [ 470 ].…”
Section: Potential Generators Of Ec Dysfunction and Activation In Mddmentioning
confidence: 99%
“…Our previous study showed that both NA and SI were significantly associated with a higher risk of cardiac readmission in both 6 months and 18 months after the initial hospitalization in patients with heart failure [10]. A cross-sectional study on patients with coronary artery disease found that SI and NA were associated with the severity of the disease, which could be explained by the association between SI and poor health behavior, as well as a greater stress hormone reactivity associated with NA [11].…”
Section: Introductionmentioning
confidence: 95%